THE METRIC PROPERTIES OF A SPACE OF ENTIRE FUNCTIONS OF BOUNDED L -INDEX IN DIRECTION - Bandura, Andriy Ivanovych (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY. Number, 2019)
The metric properties of a space of entire functions of bounded L - index in direction are investigated. It is shown that the space of entire functions with L -index in direction less than p is of the first category in the topology generated of Iyer's metric.